2017
DOI: 10.1055/s-0037-1602763
|View full text |Cite
|
Sign up to set email alerts
|

The Human Gut Microbiome in Liver Diseases

Abstract: Recent advances in culture-independent laboratory techniques and bioinformatics have contributed to enriched characterizations of the gut microbiota and microbiome in chronic liver diseases such as alcoholic liver disease, nonalcoholic fatty liver disease, primary sclerosing cholangitis, primary biliary cholangitis, and cirrhosis. In this review, the authors focus on studies characterizing and modulating the gut microbiota and microbiome in humans. The majority of studies that characterized microbiota involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 130 publications
0
34
0
Order By: Relevance
“…Bile acids, synthesized in the liver, are metabolized by gut bacteria in intestine and are critical for maintaining the host metabolism . The changes of bile acid profiles in different liver conditions are inconsistent .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bile acids, synthesized in the liver, are metabolized by gut bacteria in intestine and are critical for maintaining the host metabolism . The changes of bile acid profiles in different liver conditions are inconsistent .…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids, synthesized in the liver, are metabolized by gut bacteria in intestine and are critical for maintaining the host metabolism. 24,28 The changes of bile acid profiles in different liver conditions are inconsistent. [4][5][6][7] Growing evidences suggested that cirrhosis is closely related with bile acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…BT promotes the immune system exacerbation (20) and further increases the risk of progression to acute levels in chronic liver failure (21,22). There is evidence on both quantitative and qualitative changes in gut microbiota composition during development of liver damage (23) and how dysbiosis impacts disease progression (24,25). As a result, the host-microbiome interaction is also unstable, and the gut epithelial barrier is affected beyond disease-derived inflammation (26).…”
Section: Discussionmentioning
confidence: 99%
“…Every human being harbors at least 4 × 10 13 colonizing microbial cells [31] and more than 10 million non-redundant microbial genes in their gut [32,33]. There is sufficient evidence that changes in microbiota impact on the progression of liver disease (elegantly summarized in recent reviews [33][34][35]) and that profound changes in the microbiota occur with the development of liver cirrhosis [36], while underlying mechanisms remain not yet fully explored. There are key players in this interaction, such as an impaired epithelial barrier, in cirrhosis known as 'leaky gut' [33][34][35], with bacteria or metabolites entering into the portal blood circulation, interacting with immune cells and reaching the hepatic microcirculation, where they interact with nonparenchymal and parenchymal liver cells.…”
Section: Gut-liver Axis and Liver Diseasesmentioning
confidence: 99%
“…There is sufficient evidence that changes in microbiota impact on the progression of liver disease (elegantly summarized in recent reviews [33][34][35]) and that profound changes in the microbiota occur with the development of liver cirrhosis [36], while underlying mechanisms remain not yet fully explored. There are key players in this interaction, such as an impaired epithelial barrier, in cirrhosis known as 'leaky gut' [33][34][35], with bacteria or metabolites entering into the portal blood circulation, interacting with immune cells and reaching the hepatic microcirculation, where they interact with nonparenchymal and parenchymal liver cells. The liver also secretes bile acids, which in turn modify the intestinal microbiome and, also, act as signaling molecules between the cirrhotic liver, the gut microbiota, and the intestine [37].…”
Section: Gut-liver Axis and Liver Diseasesmentioning
confidence: 99%